Obstrucción intestinal por oblito quirúrgico. - NUÑEZ HUERTA, Edgar; SARAVIA VILLANUEVA, Carlos (Revista Médica Herediana, 2013)
The abdominal oblito that can be formed in an involuntary way after making an invasive procedure abdominal constitutes a serious problem that is not very analyzed in the medical literature. The purpose in the presentation of this case of intestinal obstruction by oblito is to aid the support of the concept that all has not still been said about the ways of presentation of the abdominal oblito. Also to insist in the importance of the prevention and the inform of the personnel of the surgical room. The daily chore confirms that this topic is a taboo issue and that it generates dilemmas in diverse planes which magnitude is as enough as to be discussed.